Why Does Language Complexity Resist Measurement? - Joseph, John E. (Frontiers in Communication, 2021)
Insofar as linguists operate with a conception of languages as closed and self-contained systems, there should be no obstacle to comparing those systems in terms of simplicity and complexity. Even if complexity ‘trade-offs’ between sub-systems of phonology, morphology and syntax are considered, it ought to be relatively straightforward to quantify constitutive elements and rules, and assign each language system its place on a complexity scale. In practice, however, such attempts have turned up a series of problems and paradoxes, which can be seen in work by Peter Trudgill and Johanna Nichols; the latter has proposed an alternative means of measuring complexity which however presents new problems of its own. This paper makes the case that overcoming the difficulty of measuring simplicity and complexity requires confronting the normative and interpretative judgments that enter into how language systems are conceived, identified and analysed.